Evaluating and implementing social–ecological systems: A comprehensive approach to sustainable fisheries. Issue 5 (29th June 2018) - Stephenson, Robert L.; Paul, Stacey; Wiber, Melanie; Angel, Eric; Benson, Ashleen J.; Charles, Anthony; Chouinard, Omer; Clemens, Marc; Edwards, Dan; Foley, Paul; Jennings, Lindsay; Jones, Owen; et al.
Abstract: Fisheries sustainability is recognized to have four pillars: ecological, economic, social (including cultural) and institutional (or governance). Although international agreements, and legislation in many jurisdictions, call for implementation of all four pillars of sustainability, the social, economic and institutional aspects (i.e., the "human dimensions") have not been comprehensively and collectively addressed to date. This study describes a framework for comprehensive fisheries evaluation developed by the Canadian Fisheries Research Network (CFRN) that articulates the full spectrum of ecological, economic, social and institutional objectives required under international agreements, together with candidate performance indicators for sustainable fisheries. The CFRN framework is aimed at practical fisheries evaluation and management and has a relatively balanced distribution of elements across the four pillars of sustainability relative to 10 alternative management decision support tools and indicator scorecards, which are heavily focused on ecological and economic aspects. The CFRN framework has five immediate uses: (a) It can serve as a logic frame for defining management objectives; (b) it can be used to define alternate management options to achieve given objectives; (c) it can serve as a tool for comparing management scenarios/options in decision support frameworks; (d) it can be employed to create a report card for comprehensive fisheries management evaluation; and (e) it is a tool for practical implementation of an integrated social–ecological system approach.